Whipspiders (Arachnida: Amblypygi) in amber from the Early Eocene and mid-Cretaceous, including maternal care - Engel, Michael S.; Grimaldi, David A (Novitates Paleoentomologicae, 2014)
Two new genera and species of fossil whipspiders (Chelicerata: Arachnida: Amblypygi) are described from Tertiary and Cretaceous ambers of southern Asia.  Paracharonopsis cambayensis Engel & Grimaldi, new genus and species, preserved in Cambay amber of Ypresian age from western India is the first Tertiary and Asian fossil of the Paleoamblypygi, a highly relict taxon that includes the Late Carboniferous genus Graeophonus Scudder and the living West African species Paracharon caecus Hansen.  Paracharonopsis cambayensis is one of the few examples in Cambay amber of a biotic connection to Africa; most taxa show widespread or Laurasian distributions.  Kronocharon prendinii Engel & Grimaldi, new genus and species, is the first Cretaceous amber whipspider and putatively a sister group to the Phrynoidea (= Apulvillata).  The holotype female of K. prendinii is preserved with the remains of three nymphs near her, documenting the Early Cretaceous presence of the extended maternal care so distinctive for the order, and a behavioral repertoire widespread among arachnids.